The Effect of Robotics Program on Students Attitude Towards Science - Thiwagar Muniandy; Sabariah Shariff; Muralindran Mariappan (Secholian Publication, 2022)
The COVID-19 pandemic has caused a worldwide health crisis that causes severe acute respiratory infections and death. WHO recommends the use of face masks to assess the spread of the epidemic. This study was conducted to identify the community's behavior using face masks and the face masks disposal circumstance during pandemic COVID-19. The objective carried out through literature review and participating observation method involves the communities in Kg Tanjung Kapor, Kudat. A total of 65 people were randomly selected to be the sample of these observations among those who left the house. The assessed aspects include the behavior of the community using face masks and their disposal circumstance. The findings of the study are supported by a literature review that is relevant to the study. The study results showed that there are three factors related to the problem of the face mask disposal circumstance: face mask quality, attitudes and behaviors toward face mask use, and the lack of environmental awareness. Education and awareness activities should be enhanced and suggest the solution to manage the face mask disposal.